Os jogos e as brincadeiras como diretrizes para a construção do conhecimento de forma lúdica e prazerosa em crianças da educação infantil - Dias, Mönica de Fátima (2012)
From my experience in kindergarten and going through the difficulty of carrying out activities with games and activities, I realized that we need to get into the game in educational programs, and intentionality, objectives and a clear awareness of their action in relation to children's learning. Create opportunities for educators to understand the meaning and importance of play activities in early childhood education, this the most fun and meaningful for our students situations occur.